MicroRNA-30b is involved in the pathological process of diabetes mellitus induced by pancreatic cancer by regulating plasminogen activator inhibitor-1. Issue 1 (1st January 2019) - Yan, Wei; Zheng, He; Dong, Jun; Liu, Chao; Zuo, Zhongfu; Liu, Xuezheng
Abstract: This study investigated the expression of plasminogen activator inhibitor-1 (PAI-1) and microRNA (miRNA or miR)-30b in tumor tissues, blood and urine from pancreatic cancer (PC) patients with diabetes mellitus. The effect of culture supernatant of PC cells with up-regulated expression of miR-30b on β cells was also investigated. Thirty-one PC patients with diabetes mellitus and 22 PC patients without diabetes mellitus were included. PC tissues and tumor-adjacent tissues, peripheral blood and urine were collected from all PC patients. Quantitative real-time polymerase chain reaction was used to determine the mRNA and miR-30b expression; Western blotting, to determine the expression of PAI-1 protein in tissues; enzyme-linked immunosorbent assay, to determine the PAI-1 content in serum or urine and dual luciferase reporter assay, to identify direct interaction between miR-30b and PAI-1 mRNA. The proliferation of INS-1 cells was determined by MTT assay. The results showed that PAI-1 mRNA and protein expression was elevated in PC patients with diabetes in contrast to that in PC patients without diabetes. By contrast, miR-30b expression was decreased in PC patients with diabetes. miR-30b could bind with the 3′-UTR seed region of PAI-1 mRNA to regulate its expression. Overexpression of miR-30b inhibited the expression of PAI-1, altered the microenvironment surrounding PC cells and promoted the proliferation of islet β-cells. These results suggest that the expression of PAI-1 in PC patients with diabetes is up-regulated, being correlated with the reduced expression of miR-30b. miR-30b is involved in the pathological process of diabetes mellitus induced by PC by regulating PAI-1.